Studies on two unexploited fish species: Peristedion adeni and Peristedion weberi - J. Shenoy, A.V, Lekshmy Nair, A. Stephen (Fishery Technology, 2021)
The chemical composition and nutritional quality of Peristedion adeni and Peristedion weberi, two unexploited fish species available in abundance in the Exclusive Economic Zone of India are reported. Size of the fish is small and separation of edible meat is difficult. Best method of utilization of the fish is conversion into meal. Meals having crude protein content varying from 55.0 to 57.0%, ash content from 17.0 to 19.6% and fat content from 17.7 to 18.1% can be prepared from the two species of fish. PER values of the meals are lower than that of casein. Amino acid analysis showed that isoleucine, leucine and valine are not present in the meals in adequate quantities compared to the FAO/WHO (1973) prescribed pattern.